2012
DOI: 10.5267/j.msl.2012.09.029
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid TOPSIS-BSC method for strategic planning

Abstract: For years, tangible assets used to be the most important precious wealth of organizations. However, the recent advances in technology has changed this concept and today, intangible assets such as human resources, customers, processes are playing essential roles on making strategies. In this paper, we present a study to setup appropriate strategies using the implementation of balanced score card in four perspectives of customers, processes, learning and financial. The proposed study of this paper gathers import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results of their survey indicated that the university was not in good condition in terms of research activities but it had maintained good condition in terms of other perspectives such as educational, infrastructure, etc. Shojaee et al (2012) presented a study to setup appropriate strategies using the implementation of BSC in four perspectives of customers, processes, learning and financial. They gathered important factors through three various brainstorming sessions and prioritized them using TOPSIS method.…”
Section: Introductionmentioning
confidence: 99%
“…The results of their survey indicated that the university was not in good condition in terms of research activities but it had maintained good condition in terms of other perspectives such as educational, infrastructure, etc. Shojaee et al (2012) presented a study to setup appropriate strategies using the implementation of BSC in four perspectives of customers, processes, learning and financial. They gathered important factors through three various brainstorming sessions and prioritized them using TOPSIS method.…”
Section: Introductionmentioning
confidence: 99%
“…According to Shojaee et al (2012), tangible assets used to be the most important precious wealth of organizations. However, the recent advances in technology has changed this concept and today, intangible assets such as human resources, customers, processes are playing critical roles on making strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent advances in technology has changed this concept and today, intangible assets such as human resources, customers, processes are playing critical roles on making strategies. Shojaee et al (2012) presented a study to setup appropriate strategies by implementing BSC in four perspectives of customers, processes, learning and financial. They gathered important factors through three brainstorming sessions and prioritized them based on TOPSIS method.…”
Section: Introductionmentioning
confidence: 99%